Bark biomass and nutrient concentrations in tropical secondary forest trees of Malaysia - Tanaka, Kenzo; Daisuke, Hattori; Paulus, Meleng; Mohd Effendi, Wasli (Elsevier B.V., 2024)
Given the high-level physiological functions and nutrient concentrations of bark that cover the entire trunks of huge trees, research into bark nutrient traits and the development of models that estimate the bark biomass of tropical trees is essential when it is sought to understand forest nutrient cycling and tree ecological traits. This study investigated the concentrations of six bark nutrients (nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and sodium (Na)) by individual tree size and the soil nutrient concentrations for two major pioneer species (Macaranga gigantea and M. hosei) of Malaysia. To estimate bark biomass, allometric equations using tree diameter, height, and crown diameter were developed by combining previous data from adjacent forests with the present data. We found no significant relationship between tree size and most bark nutrient concentrations, though all nutrient concentrations of the two pioneer trees were significantly higher than those of primary forest tree species. Surprisingly, no relationship was found between the soil and bark nutrient concentrations for either species. All the size parameters used in the allometric equations accurately estimated bark biomass. There were no differences in equations between the two species when diameter served as an explanatory variable, but differences were apparent when height and crown diameter were so used. A comparison of allometric equations that yielded the bark biomasses of different types of forest showed that the bark biomass of the tropical secondary forest trees was less than half of that of tropical dry forest trees of the same diameter. Thus, the use of inappropriate equations and nutrient concentrations increases the possibility of serious errors in estimating bark biomass and forest nutrient cycles.